United States amphibian imports pose a disease risk to salamanders despite Lacey Act regulations - Patrick J. Connelly; Noam Ross; Oliver C. Stringham; Evan A. Eskew (Communications Earth & Environment, 2023)
Abstract Batrachochytrium salamandrivorans (Bsal), one of two fungal pathogens that cause the deadly amphibian disease chytridiomycosis, is a major impending threat to salamander biodiversity in North America, where it is not yet known to occur. In the United States, a 2016 wildlife trade policy restricted trade in 20 salamander genera in attempts to prevent Bsal introduction. However, little comprehensive data is available to evaluate the impact of this policy action. Here we collate a dataset of United States amphibian imports from 1999 to 2021 using Law Enforcement Management Information System (LEMIS) data and show that reported legal trade in the targeted taxa was effectively reduced by the ban. Unfortunately, amphibian trade into the United States continues to risk Bsal introduction given that other species and genera now known to carry Bsal are still traded in large quantities (millions of live individuals annually). Additional policy responses focused on Bsal carrier taxa, especially frogs in the genus Rana, could help mitigate the impact of Bsal on North American salamanders.